Petrografia e geoquímica dos granitos pedra do sal e jurema, Parnaíba – Piauí - ARAGÃO, Arthur Jeronimo Santana (2019)
The coastal region of Piauí State comprises paleozoic sedimentary deposits from Parnaíba Basin. This region is located between two big important geologic/geotectonic units, which are The Borborema Province and a São Luís Craton fragment. In the western part of the area, is located the São Luis Craton fragment, which comprises granitoids and paleoproterozoic Metavulcanosedimentary sequences, exposed in erosive and tectonic windows surrounded by sedimentary rocks. The São Luis cratonic fragment is surrounded by the neoproterozoic Gurupi Belt. On the other hand, in the east part of the area is located the Borborema Province, characterized by its complexity and large varity of metamorphic, igneous and sedimentary rocks, that represent important time markers of different types and natures. This search studied Pedra do Sal and Jurema Granites, whose bodies are isolated from the regional sedimentary rock cover, and are exposed though an erosive windows. Petrography has revealed that Pedra do Sal Granite is a coarse-grained faneritic rock, with granitic texture, and classified as a biotite-hornblende monzogranite, still having a milonitic band that locally modify the trame. On the other hand, Jurema Granite is petrographically described as a mediun-grained faneritic rock, with granitic texture, high deformation and classified as moscovite-biotite microsienogranite. In terms of geochemical composition, Pedra do Sal Granite is metaluminous, Tipe I and its geochemical signature indicates late orogenic intraplate tectonic environment, while Jurema granite is peraluminous, Tipe S and comprises sin-colisional magmatic arc environment. Its REE distribution sugests strong fractionation, more acentuated in light REE, and soft Europium anomaly. When compared, both granites do not show important similarities. So they cannot be correlated and also diverge in petrographic aspects with Chaval Granite. However, their petrographic and geochemical aspects are compatible to São Luis Craton and Gurupi Belt granites, like Negra Velha Granite, that is a metaluminous, tipe I monzogranite with anfibole and biotite, formed in late tectonic environment; and the two micas, peraliminous, tipe S granites from Tracuateua Suite, that are similar to Jurema Granite.